RAGAM DAN POLA SEBARAN HOAKS JELANG PEMILIHAN UMUM SERENTAK TAHUN 2019 - Dewi Sad Tanti; M.T. Hidayat M.T. Hidayat (Universitas Mercu Buana, 2020)
This research is intended to map the variety of themes and patterns of spread of hoaxes related to the Simultaneous General Election in 2019. This mapping is part of an effort to identify the types and patterns of distribution so that it becomes the basis for a more efficient process of anticipating, handling and clarifying hoaxes. Using a content analysis approach will be mapped about themes, actors or objects as well as patterns of distribution and models of clarification developed in the Hoax Issue Report of the Ministry of Communication and Information. The selection of the institution is because it has the duty to supervise cyber media content while developing a campaign to reduce the spread of hoaxes in Indonesia.